De la hârtie la ecran: provocările în utilizarea intrărilor de dicționar de date pentru dezvoltarea instrumentului lemi de stabilire a lizibilității literaturii române - Mădălina Chitez; Roxana Rogobete; Karla Csürös (Revista de Istorie și Teorie Literară)
This paper addresses an interdisciplinary linguistic theme, located at the intersection between the fields of applied linguistics, computational linguistics and education: the use of Romanian dictionary data of archaisms, regionalism and main vocabulary for the creation of a digital tool for establishing the legibility of texts in Romanian for school reading. As many of the texts offered for reading to the Romanian school population are Romanian literature texts, this tool can be used to evaluate the legibility of Romanian literature texts in general. By legibility, we refer to the concept of readability, taken from English literature, which refers to the ease with which a text can be read and understood by readers. This concept incorporates factors such as vocabulary complexity, sentence structure, basic vocabulary level, and a host of other variables that can be quantified and analyzed automatically. Most of the time, the legibility of a text is given by mathematical formulas that include various indices that quantify elements such as the length of words, the complexity of phrases, and the frequency of use of certain terms. The purpose of the readability assessment is to determine whether a text is appropriate for the level of knowledge and language skills of its readers. For the Romanian language, but also for the special case of school literature texts, such formulas have not yet been tested. In the sections below, we will provide details about the LEMI platform, but also about the construction of the readability formula, insisting on the challenges created by the lack of data in digital format – dictionaries of regionalisms, archaisms, and also basic vocabulary – in order to improve the formula originally created.